DEVELOPMENT OF ISLAMIC ECONOMIC IDEAS BY AL-MAWARDI WITH MONZER KAHF (IAIN Kendari, 2023)
Islamic economics has emerged since the time of the Prophet Muhammad SAW. Islam has regulated from the beginning the relationship between humans entirely. Since the time of the Prophet, the mujtahids of Islam have formulated Islamic economic Thinking based on the Qur'an and Hadith. This research explores Islamic economic thought through Muslim figures Al-Mawardi and Monzer Kahf. This research uses a descriptive qualitative approach using a literature study of collecting information and data sourced from various libraries such as journal articles, books, the Internet, and similar previous research results aimed at obtaining information. The results showed that Al-Mawardi formulated Islamic economic ideas such as the establishment of imamah, infrastructure by the state, fulfillment of needs by the state, spending on public services financed by the state, and the establishment of baitul Mal. while Monzer Kahf formulated Islamic economic ideas such as economic activities with Islamic principles run by ibadurrahman, the scale of the dimensions of not only the world but also the afterlife, free from usury, consumption patterns that are not excessive, and the state as the maker of policy and supervision.